Polyorchidism: case report and literature review - . Elmadani, Ahmed E; A. Elmahi, Ibrahim; Hamdoun, Anas; Taha, Taha O; E Ibrahim, Mohamed; Elamir, Farouk; Taha, Osman (Gezira Journal of Health Sciences, 2008)
Polyorchidism is a rare congenital anomaly frequently associated with maldescent testis, hernia, and torsion. Reports in the literature show an increased risk of testicular malignancy in the presence of polyorchidism. This entity has characteristic sonographic features and the diagnosis is often made on the basis of sonography. A conservative approach is the treatment of choice in uncomplicated cases. We report a male of 26-years old with 2 testicles in right side diagnosed by ultrasound. A brief history and review of the literature is also presented